Packing soft spheres: experimental demonstrations with hydrogels - Hutzler, Stefan; Weaire, Denis (My University, 2023)
We describe a number of different experimental set-ups that use hydrogel spheres to demonstrate dense packings of deformable spheres in various geometries. The arrangements are similar to those of bubbles in foams, drops in emulsions, biological cells, etc. The experiments are easy to perform in the class-room or an undergraduate science laboratory. They are described in the context of the history of packing problems to which this convenient system, not yet fully explored, can add significant new findings.
PUBLISHED
Keywords: Buckling; Columnar structures; Dense packings; Packing fraction; Hydrogel; Soft spheres